Burn Effects on Soil Aggregate Stability and Water Repellency of Two Soil Types from East and North Tunisia. Issue 7 (12th April 2019) - Ibrahimi, Khaled; Mowrer, Jake; Amami, Roua; Belaid, Abdelhamid
ABSTRACT: To date, evidence of the potential effects of burning practices on soil properties in Tunisia is limited. In order to address this issue, we carried out laboratory investigations of the effects of burning on soil aggregate stability (AS) and water repellency (WR) of a clayey and a sandy loam Fluvisol soils. The treatments included low (100°C, LT), medium (300°C, MT) and high (600°C, HT), heating temperatures. Unburned (0°C, UB) soil samples were used as a control. Two breakdown mechanisms, fast wetting (FW) and mechanical breakdown (MB), were used for the measurement of AS. The latter is expressed by calculating the mean weight diameter (MWD). The water drop penetration time (WDPT) was used to evaluate the soil WR. The results showed that the unburned clayey and sandy loam soils are poorly aggregated. The HT and MT treatments significantly (p < 0.05) increased MWD of both soils, compared to UB samples, following the FW stability test. A lesser increase of MWD was observed with the MB test. The LT treatment did not significantly (p < 0.05) affect the soils AS. For the unburned clayey soil, the FW and MB tests gave significantly (p < 0.05) different MWDs . In contrast, the unburned sandy loam soil had similar MWDs under both tests. As for water repellency, the sandy loam soil was initially wettable and the clayey soil slightly water repellent. Burning treatments did not affect the sandy loam soil behavior but caused a decrease of clayey soil WR.